Infection prevention measures for patients undergoing hemodialysis during the COVID-19 pandemic in Japan: a nationwide questionnaire survey - Yuka Sugawara; Masao Iwagami; Kan Kikuchi; Yoko Yoshida; Ryoichi Ando; Toshio Shinoda; Munekazu Ryuzaki; Hidetomo Nakamoto; Ken Sakai; Norio Hanafusa; Naoki Kashihara; Masaomi Nangaku; et al. (Renal Replacement Therapy, 2021)
Abstract Background Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has become a global pandemic affecting a variety of medical treatments, including hemodialysis. This study aims to investigate the implementation of infection control measures, to examine the shortage of personal protective equipment (PPE) and disinfectants, and to quantify the number of nosocomial COVID-19 transmissions in hemodialysis facilities in Japan during the pandemic. Methods We conducted a nationwide questionnaire survey between 20 October and 16 November 2020 (i.e., between the “second wave” and “third wave” in Japan) in the 4198 dialysis facilities of the Japanese Association of Dialysis Physicians and the Japanese Society for Dialysis Therapy. A total of 2227 facilities (53.0%) responded. The questionnaire consisted of (i) characteristics of facilities, (ii) infection prevention measures in routine dialysis practices, (iii) shortage of PPE, (iv) feasibility of various isolation measures, and (v) nosocomial transmission. Results Half of the responding facilities were hospitals with multiple departments, and the other half were clinics specialized in dialysis. Several infection prevention measures such as health checks of staff and patients, donning of masks before and after hemodialysis, and disinfection of frequently contacted areas were implemented during the COVID-19 pandemic. There was a significant improvement in the implementation rate of these measures during the pandemic, compared to before it, which reached over 90%. More than half of the facilities reported a shortage of disposable masks (67.2%) and hand sanitizer alcohol (56.7%). Isolation of COVID-19 patients in private rooms was possible only in 52.7% of the facilities. The majority of facilities (73.3%) could not accept COVID-19 dialysis patients due to lack of space and manpower. Nosocomial transmission of COVID-19 occurred in 4.0% of the facilities. Of those infected, 51.9% were staff. Conclusions This survey revealed that most hemodialysis facilities in Japan had improved implementation of infection control measures and had shortage of PPEs and disinfectants, though some facilities did not implement infection prevention measures adequately, mainly due to the limited space of the facility. It may be recommended that each facility immediately establishes isolation measures to prepare for the pandemic of COVID-19.